Magnetic powder and granules, method for manufacturing magnetic powder and granules, and method for manufacturing rare earth magnets

JP2026166834APending Publication Date: 2026-10-14HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025060048
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0016】 以上の態様によれば、過電流損失が低減された希土類磁石の材料となる磁性粉粒体、磁性粉粒体の製造方法、及び、磁性粉粒体から希土類磁石を製造する希土類磁石の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166834000001_ABST
    Figure 2026166834000001_ABST
Patent Text Reader

Abstract

To provide magnetic powders and granules that serve as materials for rare earth magnets with reduced overcurrent loss, a method for manufacturing magnetic powders and granules, and a method for manufacturing rare earth magnets from magnetic powders and granules. [Solution] The magnetic powder granules 6 contain multiple stacked, flaky rare earth magnetic powders 7, the thickness of the magnetic powder granules 2 in the stacking direction is 0.15 mm or more, the lower limit of the major axis of the rare earth magnetic powders 7 is 300 μm, and the average thickness of the rare earth magnetic powders 7 is 10 μm to 30 μm. The method for manufacturing the magnetic powder granules 6 includes a (B) binding step of binding multiple rare earth magnetic powders 7 to obtain the magnetic powder granules 6. The method for manufacturing the rare earth magnet 1 includes a (C) insulating layer formation step of forming an insulating layer on the magnetic powder granules 6 to obtain insulating magnetic powder granules 12, an (E) primary molding step of arranging multiple insulating magnetic powder granules 12 in layers to obtain a primary molded body 14, and a (F) hot plastic deformation step of performing hot plastic deformation on the primary molded body 14 to obtain the rare earth magnet 1.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to magnetic powder particles that are a material for rare earth magnets, a method for producing the magnetic powder particles, and a method for producing a rare earth magnet that manufactures a rare earth magnet from the magnetic powder particles.

BACKGROUND ART

[0002] In recent years, efforts toward realizing a low-carbon society or a decarbonized society have intensified, and research and development related to electrification technologies are being carried out for vehicles as well, in order to reduce CO₂ emissions and improve energy efficiency. One of the methods for improving energy efficiency is to enhance the efficiency of motors used as power sources. In recent years, rare earth magnets have been widely used to improve motor efficiency. Further, there is a demand for improving the magnetic properties of rare earth magnets. Since rare earth magnets are metallic magnets with low electrical resistivity, they have the problem that eddy current loss tends to increase. Accordingly, there are techniques for reducing overcurrent loss in rare earth magnets.

[0003] Patent Document 1 discloses a rare earth magnet capable of reducing eddy current loss, which has rare earth magnet powder covered with a film-like coating layer containing a rare earth oxide. Between the particles of the magnet powder coated with the rare earth oxide, a binding portion containing rare earth oxide particles is interposed. The rare earth magnet is produced by subjecting a mixture of the rare earth magnet powder coated with the rare earth oxide and the rare earth oxide to high-temperature pressure molding.

[0004] Patent Document 2, for the purpose of increasing the electrical resistivity of rare earth magnets, discloses Nd2Fe 14 A method for producing a rare earth magnet is disclosed, in which magnet powder made of an alloy mainly composed of a B compound is mixed with one or two or more insulating compounds selected from oxides such as CaO, nitrides such as BN, or fluorides such as CaF₂, and this mixture is subjected to hot plastic working to obtain an anisotropic magnet material.

[0005] Patent Document 3 discloses a first method for manufacturing rare earth magnets, comprising the steps of: preparing isotropic quenched powder such as Nd-Fe-B magnet powder; mixing the isotropic quenched powder with a predetermined compound that will form an insulating layer; cold forming (pre-forming) the mixture; hot forming (densifying) the cold-formed body; and hot plastic working (anisotropizing). It is stated that the magnets manufactured by this method have a structure in which Nd-Fe-B quenched powder with a long side of 100 to 400 μm and a thickness of 20 to 40 μm is generally stacked on top of each other via compound powder. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Patent No. 4784173 [Patent Document 2] Japanese Patent Publication No. 2003-22905 [Patent Document 2] Japanese Patent Publication No. 2010-27852 [Overview of the project] [Problems that the invention aims to solve]

[0007] The rare earth magnet described in Patent Document 1 uses an insulator made of dysprosium oxide (Dy2O3) as the rare earth oxide. Since dysprosium oxide is hygroscopic, the magnetic properties of the rare earth magnet may be reduced by water adsorbed on the dysprosium oxide. In the method for manufacturing a rare earth magnet described in Patent Document 2, in the mixing step in which Nd-Fe-B magnet powder and an insulating compound are mixed, the magnet powder is pulverized and excessively subdivided, increasing the specific surface area of ​​the magnet powder and making it more susceptible to oxidation. As a result, the rare earth magnet may be oxidized, which may reduce its magnetic flux density.

[0008] In the rare earth magnet manufacturing method described in Patent Document 3, compound A, which is at least one selected from the group consisting of fluorides, oxides, and inorganic salts of heavy rare earth elements, and compound B, which is a hydride of an alkaline earth metal, are reacted during the hot forming and heat treatment processes. However, side reactions such as oxidation of the magnet or improper reaction between compound A and compound B may reduce the magnetic properties of the manufactured rare earth magnet. Therefore, there is a need for rare earth magnet materials with reduced overcurrent loss, and for rare earth magnets with reduced overcurrent loss.

[0009] In view of the above background, the present invention aims to provide magnetic powders and granules that can be used as materials for rare earth magnets with reduced overcurrent loss, a method for manufacturing magnetic powders and granules, and a method for manufacturing rare earth magnets from magnetic powders and granules, thereby contributing to the improvement of energy efficiency. [Means for solving the problem]

[0010] To solve the above problems, one aspect of the present invention provides a magnetic powder material for a rare earth magnet, comprising a plurality of stacked, flake-shaped rare earth magnetic powders, wherein the thickness of the magnetic powder material in the stacking direction is 0.15 mm or more, the lower limit of the major axis of the rare earth magnetic powder is 300 μm, and the average thickness of the rare earth magnetic powder is 10 μm to 30 μm.

[0011] According to this embodiment, it is possible to provide magnetic powders that can be used as materials for rare earth magnets, with reduced overcurrent loss.

[0012] To solve the above problems, one aspect of the present invention is a method for producing magnetic powders, which includes a binding step of spraying a binder compound solution onto a rolling flow of rare earth magnetic powder to obtain magnetic powders in which a plurality of the rare earth magnetic powders are bound together in layers with the binder compound.

[0013] According to this embodiment, it becomes easier to manufacture magnetic powders and granules.

[0014] To solve the above problems, one aspect of the present invention is a method for producing a rare earth magnet that manufactures a rare earth magnet from magnetic powder particles, the method comprising: an insulating layer forming step of forming an insulating layer having insulating properties on the surface layer of a plurality of the magnetic powder particles to obtain a plurality of the insulated magnetic powder particles; a primary forming step of obtaining a primary formed body of the plurality of the insulated magnetic powder particles obtained in the insulating layer forming step; and a hot plastic working step of performing hot plastic working on the primary formed body obtained in the primary forming step to obtain a rare earth magnet.

[0015] According to this aspect, it becomes easy to reliably produce a rare earth magnet with reduced overcurrent loss from magnetic powder particles. [Effects of the Invention]

[0016] According to the above aspects, it is possible to provide magnetic powder particles that serve as a material for a rare earth magnet with reduced overcurrent loss, a method for producing the magnetic powder particles, and a method for producing a rare earth magnet that manufactures a rare earth magnet from the magnetic powder particles. [Brief Description of the Drawings]

[0017] [Figure 1] Schematic cross-sectional view of the rare earth magnet according to the embodiment [Figure 2] Schematic cross-sectional view of the magnetic powder particles according to the embodiment [Figure 3] Diagram showing the method for producing a rare earth magnet according to the embodiment [Figure 4] Schematic diagram of a tumbling fluidizing apparatus [Figure 5] Graph showing the magnitude of the eddy current loss reduction effect of a rare earth magnet manufactured from magnetic powder particles, relative to the thickness of the magnetic powder particles in the lamination direction [Figure 6] Graph showing the magnetic properties of a rare earth magnet manufactured from magnetic powder particles, relative to the concentration (wt%) of the binder compound in the magnetic powder particles [Figure 7] Diagram showing the difference in the degree of binding of the rare earth magnetic powders 7 due to the difference in the weight average molecular weight of the binder compound [Figure 8] This is a schematic side view of two rare earth magnetic powders bound to each other by a binder compound solution. [Mode for Carrying Out the Invention]

[0018] Hereinafter, a rare earth magnet 1 according to an embodiment of the present invention will be described in detail with reference to the drawings. In the following description, the numerical range indicated by "XX to YY" means "no less than XX and no more than YY" unless otherwise specified.

[0019] <Structure of Rare Earth Magnet 1> Figure 1 is a schematic cross-sectional view of the rare earth magnet 1 of the embodiment. As shown in Figure 1, the rare earth magnet 1 includes a plurality of insulated magnet powder particles 2 arranged in layers. The insulated magnet powder particles 2 each have a plurality of laminated scaly (flake-shaped) rare earth magnet powders 3, and an insulating layer 4 formed on the surface layer of the insulated magnet powder particle 2 and having insulating properties. The insulating layer 4 covers the outer peripheral surfaces of the laminated rare earth magnet powders 3.

[0020] The rare earth magnet powder 3 is preferably a scaly neodymium magnet (Nd-Fe-B based magnet, specifically Nd2Fe 14 B).

[0021] The insulating layer 4 includes a plurality of fluoride nanoparticles 4A made of a fluoride, which are particles made of calcium fluoride (CaF2). Calcium fluoride (CaF2) has a melting point higher than that of the rare earth magnet powder 3, and exhibits poor reactivity with the rare earth magnet powder 3. The particle diameter of the fluoride nanoparticles 4A is preferably 1 to 100 nm.

[0022] The fluoride nanoparticles 4A may be particles made of an insulating inorganic fluorine compound. The fluoride nanoparticles 4A preferably have a melting point higher than that of the rare earth magnet powder 3 and exhibit poor reactivity with the rare earth magnet powder 3. Because the melting point is higher than that of the rare earth magnet powder 3 and the reactivity with the rare earth magnet powder 3 is poor, the fluoride nanoparticles 4A are preferably nanoparticles made of alkali metal fluorides such as lithium fluoride, or nanoparticles made of alkaline earth metal fluorides such as magnesium fluoride, barium fluoride, or strontium fluoride. The insulating layer 4 may also contain, as fluoride nanoparticles 4A, a plurality of nanoparticles made of alkali metal fluorides and a plurality of nanoparticles made of alkaline earth metal fluorides. Furthermore, the insulating layer 4 may also contain nanoparticles containing alkali metal fluorides and alkaline earth metal fluorides as fluoride nanoparticles 4A.

[0023] As described later, during the manufacturing process of the rare earth magnet 1 (Figure 3 (F) Hot Plastic Working Process), the rare earth magnet powder 3 is heated while being pressurized in a direction perpendicular to the main surface (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The orientation of the crystal grains of the rare earth magnet 1 as described above, and the magnetization as described above, increases the squareness ratio of the rare earth magnet 1.

[0024] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of insulating magnet powders 2 having an insulating layer 4 on its surface. The rare earth magnet 1 has a high electrical resistivity because it consists of multiple insulating magnet powders 2 isolated from each other by the insulating layer 4. This reduces the overcurrent loss of the rare earth magnet 1. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and can reduce the overcurrent loss of the rare earth magnet 1.

[0025] <Structure of magnetic powder 6> Figure 2 is a schematic cross-sectional view of the magnetic powder granules 6 of the embodiment. The magnetic powder granules 6 is the material for the rare earth magnet 1. As shown in Figure 2, the magnetic powder granules 6 includes a plurality of stacked, flaky rare earth magnetic powders 7 and a binder compound layer 8 that binds the rare earth magnetic powders 7 together. The thickness of the magnetic powder granules 6 in the stacking direction is 0.15 mm or more and 1 mm or less.

[0026] The composition of rare earth magnetic powder 7 is the same as that of rare earth magnet powder 3. Rare earth magnetic powder 7 is a flaky rare earth magnet. The lower limit of the major axis of rare earth magnetic powder 7 is 300 μm. The average thickness of rare earth magnetic powder 7 is 10 μm to 30 μm. Rare earth magnetic powder 7 is a flaky neodymium magnet (Nd-Fe-B type magnet, more precisely Nd2Fe 14 B) is preferable. The rare earth magnetic powder 7 is anisotropic, but may also be isotropic. Anisotropy is the property that the crystal orientations (easy magnetization axis, c-axis) are aligned in a specific direction. Isotropy is the property that the crystal orientations are not aligned in a specific direction.

[0027] The binder compound layer 8 is located between adjacent rare-earth magnetic powders 7 and binds them together. The binder compound layer 8 consists of a binder compound. The binder compound is an acrylic polymer with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposable, decomposing at a temperature lower than the melting point of the rare-earth magnetic powders 7.

[0028] The binder compound can be any compound capable of binding the rare earth magnetic powder 7. The binder compound has a weight-average molecular weight greater than 100,000, but does not necessarily have to be 300,000 or less. Furthermore, the binder compound does not have to be an acrylic polymer. The binder compound should preferably be a resin.

[0029] <Method for manufacturing rare earth magnet 1> Figure 3 is a diagram showing a method for manufacturing a rare earth magnet 1. As shown in Figure 3, the method for manufacturing a rare earth magnet 1 includes (A) a magnetic powder manufacturing step for manufacturing rare earth magnetic powder 7, (B) a binding step for obtaining magnetic powder granules 6 by binding the rare earth magnetic powder 7 in layers, (C) an insulating layer formation step for obtaining insulating magnetic powder granules 12 by forming an insulating layer 11 on the magnetic powder granules 6, (D) a binder removal step for obtaining degreased magnetic powder granules 13 by removing binder compounds contained in the insulating magnetic powder granules 12 by thermal decomposition, (E) a primary molding step for obtaining a primary molded body 14 by primary molding of the degreased magnetic powder granules 13, and (F) a hot plastic deformation step for obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14.

[0030] (A) The magnetic powder manufacturing process is a process for manufacturing rare earth magnetic powder 7 in the form of flakes of a predetermined size. (A) The melt spinning method is preferably used in the magnetic powder manufacturing process. As shown in Figure 3(A), the melt spinning method is a method for obtaining thin plate-shaped magnets by spraying rare earth magnets, which have been heated to a liquid state, onto a roll and then cooling it. The composition of the rare earth magnets to be liquefied is the same as the composition of the rare earth magnet powder 3. Furthermore, the thin plate-shaped magnets are crushed to obtain minute magnet fragments 16. Then, the rare earth magnetic powder 7 is classified from the minute magnet fragments 16 to obtain the rare earth magnetic powder 7. Note that the melt spinning method is not required in the magnetic powder manufacturing process. (A) The magnetic powder manufacturing process may also be a process for obtaining rare earth magnetic powder 7 by crushing thin plate-shaped rare earth magnets.

[0031] The rare earth magnetic powder 7 becomes more brittle as its thickness decreases. The lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm. Furthermore, an average thickness of 20 μm is preferable for the rare earth magnetic powder 7.

[0032] The rare earth magnetic powder 7 is flaky and has a pair of main surfaces 7A. The main surface 7A is the largest of a pair of flat surfaces facing opposite directions. The rare earth magnetic powder 7 may have an aspect ratio of approximately 1 (for example, 0.7 to 1.0) when viewed from a direction perpendicular to the main surface 7A. The aspect ratio is the size of the minor axis b (minor axis diameter) relative to the major axis a (major axis diameter) of the particle (aspect ratio = minor axis b / major axis a). Here, the major axis a (major axis diameter) means the maximum Ferret diameter, and the minor axis b (minor axis diameter) means the minimum Ferret diameter. The measurement method for the major and minor axes conforms to the provisions of JIS Z8890:2017 "Evaluation of Particle Special Properties of Powders".

[0033] (B) The binding process is a process of obtaining magnetic powder granules 6 by binding multiple rare earth magnetic powders 7 in layers with a binder compound. (B) In the binding process, a rolling flow device 20 (see Figure 4) may be used to spray a binder compound solution onto the rolling rare earth magnetic powders 7, thereby binding multiple rare earth magnetic powders 7 in layers with the binder compound.

[0034] The binder compound solution is, for example, a solution containing 4 wt% of the binder compound. The solvent of the binder compound solution is preferably 2-propanol (also called "isopropyl alcohol" or "IPA"). The solvent of the binder compound solution does not have to be 2-propanol. The solvent of the binder compound solution is preferably an alcohol. To allow for easy evaporation after the rare earth magnetic powder 7 has been bonded in layers, the solvent of the binder compound solution is preferably a solvent that evaporates easily at room temperature.

[0035] Figure 4 is a schematic diagram of the rolling fluidizer 20. As shown in Figure 4, the rolling fluidizer 20 comprises a main body case 22 having a fluidized bed 21 inside for rolling and fluidizing rare earth magnetic powder 7, a rotatable blade rotor 23 defining the bottom of the fluidized bed 21, a spray nozzle 24 provided on the side of the main body case 22, and a blower (not shown) that sends a swirling flow of air into the fluidized bed 21 through the gap between the outer circumference of the blade rotor 23 and the main body case 22. The blade rotor 23 has a conical portion 23A that protrudes upward in the center and stirring blades 23B that protrude upward and extend radially. The spray nozzle 24 is attached to the main body case 22 so that it can spray a binder compound solution toward the bottom of the fluidized bed 21.

[0036] (B) In the binding process, the rare earth magnetic powder 7 is placed in the fluidized bed 21. The blade rotor 23 is rotated, and a swirling flow of air in the fluidized bed 21 is generated by the blower. This causes the rare earth magnetic powder 7 in the fluidized bed 21 to tumble and flow. In this state, the binder compound solution is sprayed onto the tumbled rare earth magnetic powder 7 from the spray nozzle 24. Here, the binder compound solution is sprayed at a rate of 5 g / min to 30 g / min per 1 kg of tumbled rare earth magnetic powder 7.

[0037] The rare earth magnetic powder 7 is bound by a sprayed binder compound solution. Here, the binder compound solution binds between the main surfaces 7A of adjacent rare earth magnetic powders 7. The solvent (IPA) evaporates from the binder compound solution binding the rare earth magnetic powders 7. Then, a magnetic powder granule 6 is obtained in which multiple rare earth magnetic powders 7 are bound in layers by the binder compound. Here, binding in layers means that multiple rare earth magnetic powders 7 are bound with their main surfaces 7A facing the same direction. The magnetic powder granule 6 is a stack of multiple rare earth magnetic powders 7 in the shape of stacked flakes. "Stacked flake-shaped rare earth magnetic powders 7" means multiple rare earth magnetic powders 7 that are stacked with their main surfaces 7A facing the same direction.

[0038] In the magnetic granular material 6, the binder compound solution that binds the rare earth magnetic powder 7 is dry. The magnetic granular material 6 preferably contains 0.5 to 2.5 wt% of the binder compound. The concentration of the binder compound in the binder compound solution and the amount of the binder compound solution sprayed are set so that the magnetic granular material 6 contains 0.5 to 2.5 wt% of the binder compound.

[0039] As shown in Figure 3, (C) the insulating layer formation step is a step of forming an insulating layer 11 having insulating properties on the surface of the magnetic powder granules 6 to obtain insulating magnetic powder granules 12. The insulating magnetic powder granules 12 is a powder granule in which an insulating layer 11 has been formed on the magnetic powder granules 6. In (C) the insulating layer formation step, a nanoparticle dispersion liquid containing a plurality of fluoride nanoparticles 4A is sprayed onto the magnetic powder granules 6, which is being rolled and flowed using a rolling flow device 20, to form an insulating layer 11 on the surface of the magnetic powder granules 6. As described above, the fluoride nanoparticles 4A in this embodiment consist of calcium fluoride (CaF2) and are nanoparticles with a particle size of 1 to 100 nm.

[0040] The nanoparticle dispersion contains, for example, 4 wt% of fluoride nanoparticles 4A and 2.5 wt% of a binder compound. As a result, the insulating layer 11 formed by drying the nanoparticle dispersion contains 38 wt% of the binder compound and 62 wt% of fluoride nanoparticles 4A. The insulating layer 11 contains 20 wt% or more of the binder compound to facilitate the formation of an insulating layer 11 with a suitable thickness.

[0041] The solvent for the nanoparticle dispersion is preferably 2-propanol (IPA). The binder compound is a compound that can bind the fluoride nanoparticles 4A, and is preferably the same compound as the binder compound used in the binding step (B). The fluoride nanoparticles 4A are dispersed in the nanoparticle dispersion. The concentration of fluoride nanoparticles 4A, the concentration of the binder compound, and the solvent in the nanoparticle dispersion may be changed.

[0042] (C) In the insulating layer formation process, as shown in Figure 4, magnetic granular material 6 is placed in the fluidized bed 21 of the rolling fluidizer 20. Then, the blade rotor 23 is rotated and a swirling flow of air in the fluidized bed 21 is generated by the blower. As a result, the magnetic granular material 6 in the fluidized bed 21 rolls and flows. In this state, a nanoparticle dispersion is sprayed onto the rolling magnetic granular material 6 from the spray nozzle 24. The sprayed nanoparticle dispersion adheres to the surface of the magnetic granular material 6 and dries. As a result, an insulating layer 11 is formed on the surface of the magnetic granular material 6, and insulating magnetic granular material 12 is obtained.

[0043] The insulating layer 11 formed as described above preferably contains a plurality of fluoride nanoparticles 4A having a particle size of 1 to 100 nm and a binder compound that binds the plurality of fluoride nanoparticles 4A together in an amount of 20 wt% or more.

[0044] (D) The binder removal step is a step in which the insulating magnetic powder granules 12 is heated to a temperature above the thermal decomposition temperature of the binder compound, causing the binder compound to decompose thermally, and thereby obtaining degreased magnetic powder granules 13 by removing the binder compound from the insulating magnetic powder granules 12.

[0045] (D) In ​​the binder removal step, the insulating magnetic powder granules 12 may be heated in the mold of the hot press machine. As shown in Figure 3(D), the mold 30 of the hot press machine has a cylindrical mold body 31 and an upper mold 32 and a lower mold 33 that can apply a compressive force in a first direction to the object inside the mold body 31. In Figure 3, the first direction is the vertical direction, but the first direction may be a direction other than the vertical direction.

[0046] (D) In ​​the binder removal process, the insulating magnetic powder granules 12 placed in the mold body 31 of the mold 30 are heated to a temperature above the thermal decomposition temperature of the binder compound (e.g., 300°C to 400°C) for a predetermined time (e.g., 2 to 4 hours) in a reduced pressure environment or in an inert gas stream, without being pressurized by the mold 30 (upper mold 32 and lower mold 33). The inert gas is a gas that has poor reactivity with the rare earth magnetic powder 7. The inert gas is preferably a noble gas, for example. The inert gas is preferably helium gas. Air may be used instead of the inert gas.

[0047] The products of the thermal decomposition of the binder compound are discharged from the mold 30. The binder compound is preferably an acrylic polymer (polymethyl methacrylate) with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposed into the monomer methyl methacrylate. The decomposition products generated by the thermal decomposition of the binder compound volatilize and are discharged from the mold 30.

[0048] (D) When the insulating magnetic powder granules 12 are heated under reduced pressure in the binder removal process, the mold body 31 (mold 30) is heated under reduced pressure while the insulating magnetic powder granules 12 are heated. In this case, the decomposition products of the binder compound (for example, the monomer methyl methacrylate) become more volatile due to being in a reduced pressure environment and are more easily discharged outside the mold body 31 (mold 30). In addition, the decomposition products of the binder compound are less likely to accumulate around the insulating magnetic powder granules 12, and their reaction with the rare earth magnetic powder 7 and subsequent degradation of the rare earth magnetic powder 7 are suppressed.

[0049] When heating insulating magnetic powder granules 12 in an inert gas stream, the insulating magnetic powder granules 12 are heated while the inert gas is flowed inside the mold body 31 (mold 30). This makes it easier for decomposition products of the binder compound (e.g., methyl methacrylate monomer) to be discharged outside the mold body 31 (mold 30) by the inert gas stream. In addition, the decomposition products of the binder compound are less likely to accumulate around the insulating magnetic powder granules 12, and their reaction with the rare earth magnetic powder 7, which degrades the rare earth magnetic powder 7, is suppressed. It is preferable that the inert gas be heated to a temperature above the thermal decomposition temperature of the binder compound before being introduced into the mold 30. This promotes the thermal decomposition of the binder compound because it is heated by the inert gas.

[0050] (E) The primary molding step is a step of pressurizing a plurality of degreased magnetic powder particles 13 to obtain a primary molded body 14. (E) A mold 30 may be used in the primary molding step. (E) The primary molding step is a step of primary molding the degreased magnetic powder particles 13 obtained by removing the binder compound from the insulating magnetic powder particles 12 to obtain a primary molded body 14. (E) The primary molding step may be considered as a type of step of arranging a plurality of insulating magnetic powder particles 12 obtained in the (C) insulating layer forming step in layers to obtain a primary molded body 14 in which the plurality of insulating magnetic powder particles 12 have been primary molded.

[0051] (E) The primary molding step may be a step in which the degreased magnetic powder granules 13 are heated to a predetermined temperature in a mold 30 and a predetermined pressure is applied for a predetermined time to perform hot press molding (primary molding). Here, hot press molding may be performed at a mold temperature of 600°C to 700°C, preferably around 640°C. When the degreased magnetic powder granules 13 are pressurized in the mold 30, the multiple degreased magnetic powder granules 13 are oriented so that the main surface 7A of the rare earth magnetic powder 7 contained in the degreased magnetic powder granules 13 faces a first direction, and are stacked on top of each other in a direction perpendicular to the main surface 7A (first direction). Therefore, by hot press molding, the multiple degreased magnetic powder granules 13 are compressed and deformed in a state where they are stacked on top of each other in a direction perpendicular to the main surface (main surface 7A of the rare earth magnetic powder 7) (first direction).

[0052] (F) The hot plastic deformation process is a process of obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14 obtained in the (E) primary molding process. (F) In the hot plastic deformation process, the primary molded body 14 is heated and pressurized to a temperature at which some of the crystal grains of the rare earth magnetic powder 7 undergo a phase change to the liquid phase (the melting point of the rare earth magnetic powder 7, for example, around 850°C), thereby causing the primary molded body 14 to plastically deform.

[0053] (F) The hot plastic deformation process is carried out using a secondary molding die 40. The secondary molding die 40 has an upper press mold 41 and a lower press mold 42 that are arranged opposite each other. The primary molded body 14 is placed in the secondary molding die 40 such that the multiple degreased magnetic powder particles 13 contained in the primary molded body 14 are pressed in a direction perpendicular to the main surface 7A (first direction). During the plastic deformation process of the primary molded body 14, the c-axis direction (easy magnetization direction) of the crystal grains of the rare earth magnetic powder 7 contained in the primary molded body 14 is oriented in a direction parallel to the first direction (compression direction), so that magnetic anisotropy (uniaxial anisotropy) is exhibited in the primary molded body 14 during the plastic deformation process. The rare earth magnetic powder 3 contained in the rare earth magnet 1 is formed when the rare earth magnetic powder 7 is plastically deformed and its crystal grains are oriented in the first direction (compression direction). The rare earth magnet 1 (see Figure 1) obtained in the hot composition processing process is magnetized in the direction in which this magnetic anisotropy manifests (first direction).

[0054] (F) In the hot plastic deformation process, the degreased magnetic powder granules 13 are heated while being pressurized in a direction perpendicular to the main surface of the degreased magnetic powder granules 13 (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The crystal grains of the rare earth magnet 1 are oriented as described above, and the magnetization is performed as described above, thereby increasing the squareness ratio of the rare earth magnet 1.

[0055] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of insulating magnet powders 2 having an insulating layer 4 on its surface, and the insulating layer 4 increases its electrical resistivity. This reduces the overcurrent loss of the rare earth magnet 1. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and can reduce the overcurrent loss of the rare earth magnet 1.

[0056] Next, the effects of the rare earth magnet 1 manufactured in this manner and its manufacturing method will be explained.

[0057] The thickness of the magnetic powder granules 6 in the stacking direction is 0.15 mm or more, the lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm. The lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm, which allows for both resistance to cracking of the rare earth magnetic powder 7 and suppression of eddy currents in the rare earth magnet 1 manufactured from the magnetic powder granules 6.

[0058] Figure 5 is a graph showing the magnitude of the eddy current loss reduction effect of the rare earth magnet 1 manufactured from the magnetic powder granules 6 with respect to the thickness of the magnetic powder granules 6 in the stacking direction. As shown in Figure 5, the eddy current loss reduction effect of the rare earth magnet 1 can be greatly increased by making the thickness of the magnetic powder granules 6 in the stacking direction 0.15 mm or more. Also, the longer the major axis of the rare earth magnetic powder 7 and the greater the thickness, the easier it is for eddy currents to flow inside the rare earth magnetic powder 7. The rare earth magnetic powder 7 has a lower limit of a major axis of 300 μm and an average thickness of 10 μm to 30 μm, which sufficiently suppresses the eddy currents generated in the rare earth magnetic powder 7. Therefore, it is possible to provide magnetic powder granules 6 that can be used as the material for a rare earth magnet 1 with reduced overcurrent generation.

[0059] The magnetic powder 6 contains 0.5 to 2.5 wt% of a binder compound that binds the rare earth magnetic powder 7. The smaller the proportion of the binder compound in the magnetic powder 6, the weaker the binding force of the rare earth magnetic powder 7 becomes, making it easier for the bound rare earth magnetic powder 7 to separate during the process of manufacturing the rare earth magnet 1 from the magnetic powder 6. As a result, it becomes difficult to manufacture the rare earth magnet 1. Therefore, if the binder compound in the magnetic powder 6 is less than 0.5 wt%, it becomes difficult to manufacture the rare earth magnet 1, which is undesirable.

[0060] In the magnetic granular material 6, the higher the concentration of the binder compound, the lower the volume proportion of the rare earth magnetic powder 7 in the magnetic granular material 6. Furthermore, because the binder compound is thermally decomposed, gaps tend to form in the spaces where the binder compound was present in the magnetic granular material 6. As a result, it is thought that the higher the concentration of the binder compound in the magnetic granular material 6, the lower the density of the magnetic material in the rare earth magnet 1 tends to be, leading to a decrease in the residual magnetic flux density Br and coercivity iHc.

[0061] Figure 6 is a graph showing the magnetic properties of a rare earth magnet 1 manufactured from magnetic granular material 6 as a function of the binder compound concentration (wt%) in the magnetic granular material 6. Figure 6(A) is a graph showing the magnitude of the remanent magnetic flux density Br as a function of the binder compound concentration (wt%) in the magnetic granular material 6. Figure 6(B) is a graph showing the magnitude of the coercivity iHc of the rare earth magnet 1 as a function of the binder compound concentration (wt%) in the magnetic granular material 6. When the binder compound is present in the magnetic granular material 6 in a quantity greater than 2.5 Wt%, the remanent magnetic flux density of the rare earth magnet 1 decreases, as shown in Figure 6(A), and the coercivity iHc of the rare earth magnet 1 decreases, as shown in Figure 6(B). In other words, when the binder compound is present in the magnetic granular material 6 in a quantity greater than 2.5 Wt%, the magnetic properties of the rare earth magnet 1 manufactured from the magnetic granular material 6 decrease, which is undesirable.

[0062] Therefore, by including 0.5 to 2.5 wt% of a binder compound in the magnetic powder granules 6, it is possible to achieve both the ease of manufacturing the rare earth magnet 1 and the suitability of the magnetic properties (residual magnetic flux density Br, coercivity iHc) of the rare earth magnet 1 manufactured from the magnetic powder granules 6.

[0063] The weight-average molecular weight of the binder compound is greater than 100,000 and less than or equal to 300,000. Figure 7 shows the difference in the degree of binding of the rare earth magnetic powder 7 depending on the weight-average molecular weight of the binder compound. Figure 7(A) is an electron microscope image (SEM) of the rare earth magnetic powder 7 bound with a binder compound with a weight-average molecular weight of 100,000. As shown in Figure 7(A), when the binder compound has a weight-average molecular weight of 100,000, the rare earth magnetic powder 7 becomes difficult to bind and difficult to layer. Therefore, when the weight-average molecular weight of the binder compound is less than 100,000, it is undesirable because the rare earth magnetic powder 7 becomes difficult to layer.

[0064] Figure 7(B) is an electron microscope (SEM) image of rare earth magnetic powder 7 bound with a binder compound having a weight-average molecular weight of 300,000. As shown in Figure 7(B), when a binder compound with a weight-average molecular weight of 300,000 is used, the rare earth magnetic powder 7 is properly bound and layered. Furthermore, the larger the weight-average molecular weight of the binder compound, the less soluble the binder compound becomes in the solvent, making it difficult to prepare a binder compound solution and thus difficult to bind the rare earth magnetic powder 7. Therefore, the weight-average molecular weight of the binder compound should be greater than 100,000 and less than or equal to 300,000 to facilitate the proper binding of the rare earth magnetic powder 7.

[0065] The binder compound is thermally decomposable, meaning it decomposes at a temperature lower than the melting point of the rare-earth magnetic powder 7. This makes it easier to remove the binder compound from the magnetic powder 6 during the process of manufacturing the rare-earth magnet 1 from the magnetic powder 6.

[0066] The binder compound is an acrylic polymer. This makes it easier to remove the binder compound by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder 6, and also makes it easier to thermally decompose the binder compound so that no residue remains.

[0067] The method for producing magnetic powder 6 includes a binding step (B) in which a binder compound solution is sprayed onto a rolling rare earth magnetic powder 7 to obtain magnetic powder 6 in which multiple rare earth magnetic powders 7 are bound together in layers with the binder compound. This makes it easier to produce magnetic powder 6.

[0068] (B) In the binding process, a binder compound solution is sprayed at a rate of 5 g / min to 30 g / min per 1 kg of the rolling rare earth magnetic powder.

[0069] Figure 8 is a schematic side view of two rare earth magnetic powders 7 bound together by a binder compound solution. Figure 8(A) is a schematic side view of two rare earth magnetic powders 7 bound together by a small amount of binder compound solution 45. As shown in Figure 8(A), two rare earth magnetic powders 7 bound together by a small amount of binder compound solution 45 are bound by a weak force and are therefore easily separated. For this reason, when the amount of binder compound solution 45 sprayed per 1 kg of rare earth magnetic powder 7 is less than 5 g / min, the rare earth magnetic powders 7 that have been bound together become easier to separate. As a result, the rare earth magnetic powders 7 become less likely to bind together.

[0070] Figure 8(B) is a schematic side view of two rare-earth magnetic powders 7 bound together by an excess of binder compound solution 45. When the amount of binder compound solution 45 sprayed per 1 kg of rare-earth magnetic powder 7 exceeds 30 g / min, the binder compound solution 45 becomes excessive, as shown in Figure 8(B), and the excess amount of binder compound binds the rare-earth magnetic powders 7 together.

[0071] When the amount of binder compound solution sprayed per 1 kg of rare earth magnetic powder 7 is less than 5 g / min or more than 30 g / min, the rare earth magnetic powder 7 becomes difficult to bind. Therefore, in the binding process (B), by spraying the binder compound solution at a rate of 5 g / min or more and 30 g / min or less per 1 kg of the rolling flowing rare earth magnetic powder 7, it becomes easier to properly bind the rare earth magnetic powder 7.

[0072] The method for manufacturing the rare earth magnet 1 includes (C) an insulating layer formation step, (E) a primary molding step, and (F) a hot plastic deformation step. This makes it possible to reliably manufacture the rare earth magnet 1 with reduced overcurrent loss from magnetic powder granules 6.

[0073] The above embodiments may also be described as follows:

[0074] One embodiment is a magnetic powder material 6 for a rare earth magnet 1, comprising a plurality of stacked, flaky rare earth magnetic powders 7, wherein the thickness of the magnetic powder material 6 in the stacking direction is 0.15 mm or more, the lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm.

[0075] According to this embodiment, it is possible to provide magnetic powder granules 6 that serve as the material for a rare earth magnet 1, with reduced overcurrent loss.

[0076] One embodiment includes 0.5 to 2.5 wt% of a binder compound that binds multiple rare earth magnetic powders 7 together.

[0077] According to this embodiment, the manufacturing of the magnetic powder granules 6 is facilitated, and the magnetic properties (residual magnetic flux density Br, coercivity iHc) of the rare earth magnet 1 manufactured from the magnetic powder granules 6 can be favorably determined.

[0078] In one embodiment, the magnetic powder 6 contains a binder compound that binds together a plurality of rare earth magnetic powders 7, and the weight-average molecular weight of the binder compound is greater than 100,000 and less than or equal to 300,000.

[0079] According to this embodiment, it becomes easier to properly bind the rare earth magnetic powder 7.

[0080] In one embodiment, the magnetic powder 6 contains a binder compound that binds together a plurality of rare earth magnetic powders 7, and the binder compound is thermally decomposable, decomposing at a temperature lower than the melting point of the rare earth magnetic powders 7.

[0081] According to this embodiment, in the process of manufacturing a rare earth magnet 1 from magnetic powder 6, it becomes easier to remove the binder compound from the magnetic powder 6.

[0082] In one embodiment, the magnetic powder 6 contains a binder compound that binds together a plurality of rare earth magnetic powders 7, and the binder compound is an acrylic polymer.

[0083] According to this embodiment, the binder compound can be easily removed by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder granules 6, and the thermal decomposition of the binder compound can be easily carried out in a way that leaves no residual components.

[0084] One embodiment is a method for producing magnetic powder 6, which includes a binding step (B) in which a binder compound solution is sprayed onto rolling rare earth magnetic powder 7 to obtain magnetic powder 6 in which a plurality of rare earth magnetic powders 7 are bound together in layers with the binder compound.

[0085] According to this embodiment, it becomes easier to manufacture the magnetic powder granules 6.

[0086] In one embodiment, (B) during the binding process, a binder compound solution is sprayed at a rate of 5 g / min to 30 g / min per 1 kg of rolling rare earth magnetic powder 7.

[0087] According to this embodiment, it becomes easier to properly bind the rare earth magnetic powder 7.

[0088] One embodiment is a method for manufacturing a rare earth magnet 1 from magnetic powder granules 6, comprising: (C) an insulating layer forming step to obtain a plurality of insulating magnetic powder granules 12 by forming an insulating layer 11 on the surface of a plurality of magnetic powder granules 6; (E) a primary molding step to obtain a primary molded body 14 in which the plurality of insulating magnetic powder granules 12 obtained in step (C) are arranged in layers; and (F) a hot plastic deformation step to obtain a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14 obtained in step (E).

[0089] According to this embodiment, a rare-earth magnet 1 with reduced overcurrent loss can be reliably manufactured from magnetic powder granules 6.

[0090] This concludes the description of specific embodiments, but the present invention is not limited to the above embodiments and can be broadly modified and implemented. For example, the solvent for the binder compound solution and the nanoparticle dispersion does not have to be IPA, but may be an alcohol that is liquid at room temperature, such as 1-propanol or butanol. [Explanation of Symbols]

[0091] 1: Rare earth magnets 4: Insulating layer 6:Magnetic powder 7: Rare earth magnetic powder 11: Insulating layer 12: Insulating magnetic powder granules 14: Primary molded body 45: Binder compound solution

Claims

1. A magnetic powder material for a rare earth magnet, comprising multiple stacked, flaky rare earth magnetic powders, The thickness of the magnetic powder in the stacking direction is 0.15 mm or more. A magnetic powder material in which the lower limit of the major axis of the rare earth magnetic powder is 300 μm, and the average thickness of the rare earth magnetic powder is 10 μm to 30 μm.

2. The magnetic powder granules according to claim 1, comprising 0.5 to 2.5 wt% of a binder compound for binding a plurality of the aforementioned rare earth magnetic powders.

3. It contains a binder compound that binds multiple of the aforementioned rare earth magnetic powders, The magnetic powder material according to claim 1, wherein the weight-average molecular weight of the binder compound is greater than 100,000 and less than or equal to 300,000.

4. It contains a binder compound that binds multiple of the aforementioned rare earth magnetic powders, The magnetic powder granules according to claim 1, wherein the binder compound has thermal decomposition properties, decomposing at a temperature lower than the melting point of the rare earth magnetic powder.

5. It contains a binder compound that binds multiple of the aforementioned rare earth magnetic powders, The magnetic powder granules according to claim 1, wherein the binder compound is an acrylic polymer.

6. A method for producing magnetic powders according to any one of claims 1 to 5, A method for producing magnetic powder, comprising a binding step of spraying a binder compound solution onto the rolling flow of the rare earth magnetic powder to obtain a magnetic powder granule in which a plurality of the rare earth magnetic powders are bound together in layers with the binder compound.

7. The method for producing magnetic powder granules according to claim 6, wherein in the binding step, the binder compound solution is sprayed at a concentration of 5 g / min to 30 g / min per 1 kg of the rare earth magnetic powder that is being rolled and flowed.

8. A method for producing a rare earth magnet from magnetic powder granules according to any one of claims 1 to 5, An insulating layer forming step to obtain a plurality of insulating magnetic powder particles by forming an insulating layer on the surface of a plurality of the magnetic powder particles, A primary molding step to obtain a plurality of primary molded bodies of insulating magnetic powders obtained in the insulating layer forming step, A method for manufacturing a rare earth magnet, comprising: a hot plastic deformation step of performing hot plastic deformation on the primary molded body obtained in the primary molding step to obtain a rare earth magnet.

Citation Information

Patent Citations

  • High resistance rare earth magnet and its manufacturing method

    JP2003022905A

  • Method of manufacturing r-t-b based rare earth magnet

    JP2010027852A

  • Rare earth magnet and method for manufacturing the same

    JP4784173B2